Structural and viscoelastic relaxation in glyceral solutions of alcali-metal walides - WACIŃSKI, M.; PŁOWIEC, R. (Archives of Acoustics, 1992)
This paper presents the results of density, static viscosity and mechanical impedance measurements of glycerol solutions of electrolytes: LiBr, KBr, NaBr, KCl, RbCl, SeCl, NaF, LiF. The following quantities were calculated: limiting shear moduli, relaxation times, viscous flow activation energy and distribution parameters of viscoelastic relaxation times. Distribution parameters of viscoelastic relaxation times were determined on the basis of the Maxwell's model and the B-E-L model supercooled liquids. The occurrence of a wide spectrum of relaxation times was explained on the basis of the McDuffie's and Litovitz's cluster model and the mechanism proposed by Miles and Hammamoto. On the grounds of the achieved parameters of the relaxation time distribution width it was proved that long-range interactions (structural solvation) caused by the influence of the solvated anion decisively influence structural processes in the analysed solutions.